A view of an elevation of the Sheshashayi Vishnu Temple - Temples of India Project Team (Jio Institute, 2024)
A view of an elevation of the Sheshashayi Vishnu Temple with basal mouldings, khura, kumbha (pot-shaped), kalasha (a pitcher), antarapatta (recesses between mouldings), and kapotapalika (cyma recta moulding). The jangha (wall) is plain, while the varandika (moulded parapet) consists of two kapotapalikas and an antarapatta, topped by a gaggarika. The shikhara (superstructure) above is severely damaged.